2018
DOI: 10.1038/s41598-018-31684-z
|View full text |Cite
|
Sign up to set email alerts
|

Armchair MoS2 nanoribbons turned into half metals through deposition of transition-metal and Si atomic chains

Abstract: MoS2 nanoribbons with armchair-terminated edges are semiconductors suitable for the tuning of electronic and magnetic properties. Our first-principles density function calculations reveal that a variety of transition-metal atomic chains deposited on some of the ribbons is able to transform the semiconductors into half metals, allowing transport of 100% spin-polarized currents. Furthermore, we found that a Si atomic chain is equally capable of achieving half metallicity when adsorbed on the same nanoribbon. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…The band gap of CdS NRs was decreased with a significant shift in their respective valence and conduction band positions and also with increasing doping content of Ag + (from 2.56 to 2.29 eV) and Cu 2+ (from 2.56 to 2.31 eV) ions . Although MoS 2 NRBs with armchair-terminated edges are generally semiconducting in nature, DFT calculations revealed that they can be converted into half metals upon deposition of transition metal (e.g., Ti) atomic chains, allowing transport of 100% spin-polarized currents . The observed magnetism is considered to originate from competition between the exchange splitting and crystal-field splitting .…”
Section: Structures and Propertiesmentioning
confidence: 95%
See 1 more Smart Citation
“…The band gap of CdS NRs was decreased with a significant shift in their respective valence and conduction band positions and also with increasing doping content of Ag + (from 2.56 to 2.29 eV) and Cu 2+ (from 2.56 to 2.31 eV) ions . Although MoS 2 NRBs with armchair-terminated edges are generally semiconducting in nature, DFT calculations revealed that they can be converted into half metals upon deposition of transition metal (e.g., Ti) atomic chains, allowing transport of 100% spin-polarized currents . The observed magnetism is considered to originate from competition between the exchange splitting and crystal-field splitting .…”
Section: Structures and Propertiesmentioning
confidence: 95%
“…267 Although MoS 2 NRBs with armchair-terminated edges are generally semiconducting in nature, DFT calculations revealed that they can be converted into half metals upon deposition of transition metal (e.g., Ti) atomic chains, allowing transport of 100% spin-polarized currents. 268 The observed magnetism is considered to originate from competition between the exchange splitting and crystal-field splitting. 269 For the zigzag-terminated MoS 2 NRBs, N-doping at the S-edge or in the center changed the ground state energy level and a negative differential resistance effect was observed within a certain bias voltage range.…”
Section: Layer-dependent Propertiesmentioning
confidence: 99%
“…In recent years, two-dimensional (2D) layered semiconductor nanomaterials, such as graphene, black phosphorus, , and transition metal dichalcogenides (TMDs), have received considerable attention due to their ultrasmall sizes, excellent electronic transmissibility, and defect-free surface. However, when the width decreases to nanoscale, the motion of electrons in 2D materials would be influenced seriously by the boundary defects, the approximation of physical dimension, and the mean free path of electrons . Therefore, the band gap, optical properties, anisotropy, and electronic properties of 2D materials may change with the width and type of boundary defects, which will bring more challenges for the development of 2D devices. Hence, one-dimensional (1D) semiconductors with a small number of boundary and surface defects are highly sought, which exhibit many novel properties such as high carrier motilities, high flexibility and mechanical strength, great white-light emission, piezoelectric performance enhancement, and thermoelectric properties. Moreover, the performance of carbon nanotube transistors has already exceeded that of silicon transistors .…”
Section: Introductionmentioning
confidence: 99%
“…17 On the other hand, atomic copper (Cu) has shown various promising applications, including notable catalytic activities. 21,22 Anchoring Cu atoms with MoS 2 through substitution of S atoms might provide a stable Cu doped MoS 2 structure. For example, S vacancy substitution with group IB metal was predicted to increase the active sites in the MoS 2 monolayer, making it a suitable candidate for nucleophilic and electrophilic attacks.…”
Section: Introductionmentioning
confidence: 99%